A Comprehensive Needs Analysis of French Course for Tourism and Hospitality Program - Marliza Arsiyana; Nour Hernadi (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
This study aims to conduct a comprehensive needs analysis on french language for tourism and hospitality programs by looking closely at three points of view, i.e., 120 students of tourism and hospitality program, 7 french lecturers, and 5 hospitality professionals. This research applied a mixed-methods approach to collecting the data. This means that this study deployed a set of qualitative and quantitative measures to attain deep answers. Furthermore, the data in this study were collected through multiple instruments, including interviews and questionnaires. The result of the analysis of the data revealed that the French language was one of the significant foreign languages, besides English, that needed to be learned by the students to have a good carrier in the hospitality and tourism industry in the future. Along with that fact, speaking was considered as the most important language skill, among the other skills, which have to be developed by the students. Moreover, the ideal teaching materials urgently needed to be developed within this context were those equal to the intermediate level. The findings of this study were expected to have a further contribution to the development of comprehensive teaching syllabuses, materials, as well as lesson plans for French-language classrooms in the tourism and hospitality program.